Financial Ecological Environment, Financing Constraints, and Green Innovation of Manufacturing Enterprises: Empirical Evidence From China - Zhao, Linhai; Wang, Yajun (Frontiers in Environmental Science, 2022)
In the carbon neutrality strategy, facilitating the green innovation of enterprises and promoting industrial upgradation have become a key issue. We explore the relationship between the financial ecological environment, financing constraints, and green innovation of manufacturing enterprises based on endogenous growth and stakeholder theories. Manufacturing companies listed on Shanghai Stock Exchange and Shenzhen Stock Exchange during 2010–2020 are taken as samples. With the help of principal component analysis, a comprehensive index of the annual financial ecological environment is constructed. The SA index is employed to measure the financing constraints of firms, and the number of granted green patents is used to measure the green innovation of manufacturing enterprises. We conclude that the green innovation of manufacturing enterprises will relax their financing constraints. The financial ecological environment positively moderates the relationship between green innovation and corporate financing constraints. An excellent financial ecological environment enhances the mitigation effect of green innovation of manufacturing enterprises on their financing constraints. Policy implications are given according to the conclusion.